Analysis of Football Referee Satisfaction in Making Decision Based on Experience Levels - Nurcahya, Yudi; Kusumah, Widi; Mulyana, Dadan; Kodrat, Hikmat; Yudi Nurcahya; Widi Kusumah; Dadan Mulyana; Hikmat Kodrat (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2021)
The role of a referee is important in every football match. A referee sometimes makes mistakes which can affect the outcome of the match. Dissatisfaction with the decision given by a referee will give an impact on the performance shown in a football match. This study aimed to find out the satisfaction of football referees in making decisions in football matches based on the experience of the referee. This research is a quantitative study using descriptive research methods with a causal comparative research design. The research sample involved was the referee who served in the Indonesian League 1 match. The instrument of this study was a Soccer Referee Decision Satisfaction Scale questionnaire. Based on the results of data processing and analysis using the Independent sample T-Test, it was found that there were differences in the level of satisfaction of football referees in making decisions based on the experience of each referee. It indicates that the experience of a referee will affect the psychological aspects of the referee in making decisions.